Analisis faktor-faktor yang mempengaruhi profitabilitas bank syariah - Anggrainie, Agustina (Maliki Interdisciplinary Journal, 2023)
In this era of increasingly rapid technological developments, Islamic banks have a strategic role in supporting inclusive and sustainable economic growth. With an approach based on Islamic principles, Islamic banks promote a more just and sustainable economic development. So that this research aims to analyze the factors that can affect the profitability of Islamic banks through qualitative research methods with a literature study approach. The results of this study state that factors that can affect the profitability of Islamic banks include profit sharing spreads, financing to deposit ratios, financial ratios, distribution of financing, and operational efficiency.